Trends in Haptic Communication of Human-Human Dyads: Toward Natural Human-Robot Co-manipulation - Jensen, Spencer W.; Salmon, John L.; Killpack, Marc D. (Frontiers in Neurorobotics, 2021)
In this paper, we analyze and report on observable trends in human-human dyads performing collaborative manipulation (co-manipulation) tasks with an extended object (object with significant length). We present a detailed analysis relating trends in interaction forces and torques with other metrics and propose that these trends provide a way of improving communication and efficiency for human-robot dyads. We find that the motion of the co-manipulated object has a measurable oscillatory component. We confirm that haptic feedback alone represents a sufficient communication channel for co-manipulation tasks, however we find that the loss of visual and auditory channels has a significant effect on interaction torque and velocity. The main objective of this paper is to lay the essential groundwork in defining principles of co-manipulation between human dyads. We propose that these principles will enable effective and intuitive human-robot collaborative manipulation in future co-manipulation research.